Shoot multiplication growth of some apple cultivars with a combination of auxin and cytokinin hormones in vitro - Untung Santoso; Fatimah Nursandi; Careca Sepdihan Rahmat Hidayatullah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Apples (Malus sylvestris) have been grown in Indonesia, especially in highland areas such as Batu, Nongkojajar, and Poncokusumo. In order to propagate apple plants through in vitro, organ culture is performed in a controlled environment, free of pests and diseases. The research aimed to evaluate the effect of the composition of the growth regulator BAP-IAA on the growth and shoot multiplication of several apple cultivars in vitro. The research was carried out at the Indonesian Orchid Partners Laboratory Jl. Hasanudin 1 No 24 Junrejo District, Batu City, Indonesia. The four apple cultivars used were Fuji, Red Delicious, Gala, and Manalagi apples. Four types of growth regulator composition were the treatments: 3 mg L-1 BAP and 0.2 mg L-1 IAA, 6 mg L-1 BAP and 0.2 mg L-1 IAA, 3 mg L-1 BAP and 0.3 mg L-1 IAA, and 6 mg L-1 BAP and 0.3 mg L-1 IAA. The results showed that growth and yield were more precise in the combination of Red Delicious with the growth enhancer composition of 3 mg L-1 BAP and 0.3 mg L-1 IAA, as shown by the variable number of shoots and fresh weight of explants. The results showed that the combination of the Red Delicious apple cultivar with BAP 3 mg L-1+IAA 0.3 mg L-1 can be recommended as the best treatment in mass shoot production/multiplication. Keywords: composition; cytokinin-auxin; apple cultivars; shoot multiplication